THE CONTRIBUTION OF PARKING GUARDS IN IMPROVING FAMILY WELFARE - Zalina Fitriani (Al-Qardhu, 2023)
Pancor Terminal Market is a shopping center and gathering place for sellers and buyers. Buyers who visit will of course use vehicles and will need the services of a Parking Attendant who will help monitor and manage their vehicles. With the parking attendant service, visitors at the Pancor terminal market no longer worry about the vehicles they leave behind. Therefore, the role of the parking attendant is very important, apart from being tasked with maintaining the security of the market environment, the parking attendant also has a big responsibility to support his family's economy in order to achieve family welfare. Prosperity is a condition where a person can fulfill the needs that support a person to live in society and create a sense of security and peace physically and mentally. The research results show that family welfare can be seen from primary, secondary and tertiary needs that can be fulfilled by a family. In this case, the parking attendant contributes to improving the welfare of his family. The welfare of parking attendants after explaining the income earned from work every day, the attendants are classified as prosperous because they are able to meet the family's primary and secondary needs. If you look at the 2020 East Lombok Regency Minimum Wage (UMK), it is IDR. 2,184,197 per month parking attendant wages have met the East Lombok UMK.